A robust recognition error recovery for micro-flow cytometer by machine-learning enhanced single-frame super-resolution processing - Huang, Xiwei (2014)
With the recent advancement in microfluidics based lab-on-a-chip technology, lensless imaging system integrating microfluidic channel with CMOS image sensor has become a promising solution for the system minimization of flow cytometer. The design challenge for such an imaging-based micro-flow cytometer under poor resolution is how to recover cell recognition error under various flow rates. A microfluidic lensless imaging system is developed in this paper using extreme-learning-machine enhanced single-frame super-resolution processing, which can effectively recover the recognition error when increasing flow rate for throughput. As shown in the experiments, with mixed flowing HepG2 and Huh7 cells as inputs, the developed scheme shows that 23% better recognition accuracy can be achieved compared to the one without error recovery. Meanwhile, it also achieves an average of 98.5% resource saving compared to the previous multi-frame super-resolution processing.